The impact of temperature on labor productivity——evidence from temperature-sensitive enterprises - Zhang, Wei; Ding, Ning; Han, Yilong; He, Jie; Zhang, Na (Frontiers in Environmental Science, 2023)
Climate change increases the frequency of extreme climate events and impacts the economy and the society in a negative way. As typical climate events, temperature anomalies affect individual health and working conditions, particularly for industries that depend heavily on temperatures. Using a research setting of Chinese temperature-sensitive enterprises, we analyze the impact of temperature on labor productivity. The findings indicate an inverse U-shaped relationship between temperature and labor productivity, with labor productivity peaking at 24.90°C on average. Further analysis shows that labor productivity peaks in the eastern regions at a higher level (26.25°C) than in the central & western regions (20°C). Moreover, we note that technological innovation is crucial for enterprises to manage climate risks and maintain effective labor productivity. This study provides empirical evidence on the relationship between environmental risk and corporate operations, shedding light on the significance of corporate sustainable development against accelerating global climate change.